Sistem Informasi Gamelan Jawa: Javanese Musical Instrument Information System - iswanto (Global, 2018)
Javanese Musical Instrument a musical instrument of valuable cultural heritage owned by the Indonesian nation which is currently being favored by many Indonesian people, especially the Javanese people and also foreign communities like in European and American. Javanese Gamelan is a unique musical instrument, there are at least 13 types of musical instruments (in total there are 20 types of musical instruments) that are needed in a concert and will produce a class of music as an orchestra. Many research on Javanese Gamelan has been done, but the object taken as most research is the making of musical instrument simulations using multimedia technology, so that the public, observers and personnel of Javanese art groups find difficulty to obtain detailed information about Javanese gamelan which includes types of instruments, how to play, type of rhythm, laras and pathet, type of song and notation. In this research, a Javanese Gamelan information system is designed to manage most of the information related to Javanese gamelan as a web based application so that it is easily accessible to the public, so it can be used to increase knowledge for observers and as a reference for Javanese art groups in playing Java Instruments.